Numerical study of the viscous drop spreading process when transferring heat to a substrate of simple geometry; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Krainov A. V. Aleksander Valerievich (2015, 2015)
Title screen